Building Healthy Living Habits: Handwashing Socialization Using Soap and Flowing Water at SDN Bejalen - Faiqotul Wafiqiyah; Dewi Aminatus Sholikhah; Abizar Khipari; Nur Saidah; Laelatul Muniroh (Universitas Palangka Raya, 2024)
Clean and healthy living habits, such as washing your hands frequently with soap and running water, are very important to prevent the spread of diseases such as diarrhea and respiratory tract infections, especially in the school environment. This activity is part of efforts to improve overall health. This research aims to evaluate the effectiveness of hand washing socialization in building healthy living habits in the Bejalen Elementary School environment, Ambarawa. The method used involves a participatory approach through education and direct demonstrations. Based on the results of the activity evaluation, students understand the material by being able to answer questions correctly. Thus, integrated hand washing socialization can be a strategic step in increasing the health awareness of students at Bejalen Elementary School as well as encouraging the creation of a hygienic school environment.